2020
DOI: 10.6007/ijarbss/v10-i4/7149
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Public University Student's Impulse Purchase Behaviour in Malaysia

Abstract: The impulse purchase behaviour among the consumer could be great opportunities for every seller or retailers to increase their sales and directly the profits as well which makes this kind of behaviour are pretty much welcomed in every stores. However, it has been related to the increase of debt, wasting money, illiteracy on personal financing and lack of sense on differentiate needs and wants of a consumer. Hence, the aim of this study is to examine the factors influencing public university student's impulse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The findings of previous studies also found that the problems faced by teachers in PdP at Vocational Colleges are also due to time constraints, lack of suitable places, equipment and materials in handling PdP which are limited and not up-to-date as well as the lack of mastery of knowledge and skills in implementing VM course implementation strategies (Anuar et al, 2015;Abdullah & Ali, 2017;Jamaludin & Osman, 2014;Rahman et al, 2011). The development of the latest trend of PdP VM online (Roggeveen et al, 2021;Karim et al, 2020;Boardman & Mccormick, 2019;Mohamed et al, 2020;Hazwani & Nizar, 2016), should be highlighted by teachers to students to see the influence of different goods purchasing behavior from online store environment methods, and online promotions (Hasim et al, 2020). Therefore, this study was conducted to explore the teaching approach implemented by teachers for the Visual Merchandising (VM) course at the Vocational College.…”
Section: Problem Statementmentioning
confidence: 98%
“…The findings of previous studies also found that the problems faced by teachers in PdP at Vocational Colleges are also due to time constraints, lack of suitable places, equipment and materials in handling PdP which are limited and not up-to-date as well as the lack of mastery of knowledge and skills in implementing VM course implementation strategies (Anuar et al, 2015;Abdullah & Ali, 2017;Jamaludin & Osman, 2014;Rahman et al, 2011). The development of the latest trend of PdP VM online (Roggeveen et al, 2021;Karim et al, 2020;Boardman & Mccormick, 2019;Mohamed et al, 2020;Hazwani & Nizar, 2016), should be highlighted by teachers to students to see the influence of different goods purchasing behavior from online store environment methods, and online promotions (Hasim et al, 2020). Therefore, this study was conducted to explore the teaching approach implemented by teachers for the Visual Merchandising (VM) course at the Vocational College.…”
Section: Problem Statementmentioning
confidence: 98%
“…As the marketing stimulus, visual merchandising principles are using by retailers to attract more customers into their shops [20]. The prior studies have been examined the influence of visual merchandising stimulus such as music, light, layout on consumers' impulsive buying behavior [21,22,23]. It is evidence that hedonic values such as visually appealing designs play a critical role in satisfying experiences.…”
Section: Introductionmentioning
confidence: 99%